3-Thienylboronic Acid as a Receptor for Diol-Containing Compounds: A Study by Isothermal Titration Calorimetry - Yulia Efremenko; Vladimir M. Mirsky (Chemosensors, 2022)
The electrochemical activity of 3-thienylboronic acid and its feature to form polymer films makes it a perspective receptor material for sensor applications. The affinity properties of this compound were studied here by isothermal titration calorimetry. A number of different analytes were tested, and the highest binding enthalpy was observed for sorbitol and fructose. An increase of pH in the range of 5.5–10.6 results in the rise of the binding enthalpy with an increase of the binding constant to ~8400 L/mol for sorbitol or ~3400 L/mol for fructose. The dependence of the binding constant on pH has an inflection point at pH 7.6 with a slope that is a ten-fold binding constant per one pH unit. The binding properties of 3-thienylboronic acid were evaluated to be very close to that of the phenylboronic acid, but the electrochemical activity of 3-thienylboronic acid provides a possibility of external electrical control: dependence of the affinity of 3-thienylboronic acid on its redox state defined by the presence of ferro/ferricyanide in different ratios was demonstrated. The results show that 3-thienylboronic acid can be applied in smart chemical sensors with electrochemically controllable receptor affinity.